2013
DOI: 10.1016/j.jegh.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Polity and health care expenditures: The association among 159 nations

Abstract: This paper hypothesized that democratic nations, as characterized by Polity IV Project regime scores, spend more on health care than autocratic nations and that the association reported here is independent of other demographic, health system or economic characteristics of nations. WHO Global Observatory data on 159 nations with roughly 98% of the world's population were examined. Regime scores had significant, direct and independent associations with each of four measures of health care expenditure. For every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Studies have found associations between HDI and health system quality, health outcomes, disease prevalence, and health-seeking behavior ( 20 24 ). Polity has been associated with health metrics such as healthcare expenditures and infant mortality ( 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found associations between HDI and health system quality, health outcomes, disease prevalence, and health-seeking behavior ( 20 24 ). Polity has been associated with health metrics such as healthcare expenditures and infant mortality ( 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…One mediator was selected from sets of highly correlated mediators (ρ > 0.8), retaining the mediator with the lowest average correlation with other synovial mediators. For each virtual population, the best linear regression models were identified using an exhaustive search with the LEAPS package [28] in R. An initial analysis of the Bayesian information criterion (BIC, a widely used model selection metric that combines the explained variance and model complexity) for a subset of VPops suggested employing a model of 27 regressors. Alternatively, an analysis of adjusted R 2 for each model size found a model size of five analytes yielded an adjusted R 2 of 0.75.…”
Section: Methodsmentioning
confidence: 99%
“…In the Table, we list 10 proposed actions that, if materialized, could help alleviate disparities. These actions include the creation of a global health governance framework (Frenk and Moon, 2013), adherence to human rights and democratic principles (Gregorio and Gregorio, 2013), community empowerment (Marmot et al, 2010) and emphasis on common risk factor and prevention approaches (Sheiham et al, 2011). Examples of successful population-based approaches in reducing oral health disparities include the introduction of community water fluoridation, likely the most successful dental public health intervention to date (Riley et al, 1999).…”
Section: Proposed Actionsmentioning
confidence: 99%